The “Exo hand-2” complex in the rehabilitation of the upper limb in cerebral palsy using the non-invasive interface “brain-computer” - N. V. Larina; L. L. Korsunskaya; S. V. Vlasenko (Нервно-мышечные болезни, 2020)
Improving the function of the upper limb in cerebral palsy is one of the main tasks of rehabilitation treatment and socialization of the patient.The purpose of the study was to evaluate the effectiveness of the “Exo hand-2” complex with the non-invasive interface “brain-computer” for correcting the motor function of the upper limb in cerebral palsy.The study involved 50 male and female with cerebral palsy (main group n = 30, control group n = 20) aged 12–18 years old. The level of motor activity according to the criteria of classification of large motor functions (GMFCS) was not more than III. All patients received a standard course of spa rehabilitation for 21 days. Patients of the main group were additionally rehabilitated using the “Exo hand-2” complex with the non-invasive interface “brain-computer”. As a result of treatment in the main group, spasticity in the paretic hand on the Modified Ashworth Scale decreased from 3 (2; 3) to 2 (1; 2) points (p <0.002); according to Tardieu, spasticity decreased from the level of 3 (2; 3) to 2 (1; 2) (p <0.002). Half of the patients had paretic arm muscle strength in the Medical Research Counsil Weakness Scale sums core from 2.3 (2; 3) to 3 (2; 3) points after treatment (p = 0.002); assessment of household skills on the Modified Franchay Scale showed an improvement from 37 (22.75; 63.75) to 45 (30; 72.75) points after therapy.